Effects of exercise and cold-water exposure on microvascular muscle perfusion - Huettel, Moritz; Schroeter, Sarah; Heiss, Rafael; Lutter, Christoph; Golditz, Tobias; Hoppe, Matthias Wilhelm; Forst, Raimund; Hafez, Hossam; Engelhardt, Martin; Grim, Casper; Hotfiel, Thilo (Ultraschall in der Medizin - European Journal of Ultrasound, 2023)
Purpose Microvascular blood flow (MBF) and its intramuscular regulation are of importance for physiological responsiveness and adaptation. The quantifiable in-vivo monitoring of MBF after cycling or systemic cold-water exposure may reveal new insights into capillary regulatory mechanisms. This study aimed to assess the role of exercise and cold therapy on MBF by using contrast-enhanced ultrasound (CEUS).Methods Twenty healthy athletes were recruited and randomly assigned to an intervention (IG) or a control group (CG). MBF was quantified in superficial (rectus femoris, RF) and deep muscle layers (vastus intermedius, VI). Representative perfusion parameters (peak enhancement (PE) and wash-in area under the curve (WiAUC)) were measured after a standardized measurement protocol for both groups at resting conditions (t0) and after cycling (20 min., 70% Watt max, t1) for both groups, after cold-water immersion exposure for IG (15 min., 12°C) or after precisely 15 minutes of rest for CG (t2) and for both groups after 60 minutes of follow-up (t3).Results At t1, MBF in VI increased significantly compared to resting conditions in both groups in VI (p= 0.02). After the cold-water exposure (t2), there were no statistically significant changes in perfusion parameters as well as after 60 minutes of follow-up (t3) (p = 0.14).Conclusion Cycling leads to an upregulation of MBF. However, cold exposure does not change the MBF. The implementation of CEUS during different physiological demands may provide deeper insight into intramuscular perfusion regulation and regenerative processes.
Keywords: microvascular blood flow; cryotherapy; sports; contrast-enhanced ultrasound (CEUS)